The Relationship between Superior Disc-Endplate Complex Injury and Correction Loss in Young Adult Patients with Thoracolumbar Stable Burst Fracture - Lee, Kyu Yeol; Kim, Min-Woo; Seok, Sang Yun; Kim, Dong Ryul; Im, Chul Soon (Clinics in orthopedic surgery, 2017)
To determine the relationship between superior disc-endplate complex injury and correction loss after surgery in a group of young adult patients with a stable thoracolumbar burst fracture. The study group was comprised of young adult patients who had undergone short-segment posterior fixation and bone grafting under the diagnosis of a stable thoracolumbar burst fracture from March 2008 to February 2014. Follow-up was available for more than 1 year. Before surgery, magnetic resonance imaging was performed to determine injury to the anterior longitudinal ligament, posterior longitudinal ligament, and superior and inferior intervertebral discs and endplates. Correction loss was evaluated by the Cobb angle, intervertebral disc height, upper intervertebral disc angle, vertebral wedge angle, and vertebral body height. No significant relation was noted between correction loss and an injury to the anterior longitudinal ligament, posterior longitudinal ligament, inferior intervertebral disc/endplate, and fracture site, whereas an injury to the superior endplate alone and superior disc-endplate complex showed a significant association. Specifically, a superior intervertebral disc-endplate complex injury showed statistically significant relation to postoperative changes in Cobb angle ( = 0.026) and vertebral wedge angle ( = 0.047). A superior intervertebral disc-endplate complex injury may have an influence on the prognosis after short-segment fixation in young adult patients with a stable thoracolumbar burst fracture.